2020
DOI: 10.2196/15506
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App for Mental Health Monitoring and Clinical Outreach in Veterans: Mixed Methods Feasibility and Acceptability Study

Abstract: Background Advances in mobile health (mHealth) technology have made it possible for patients and health care providers to monitor and track behavioral health symptoms in real time. Ideally, mHealth apps include both passive and interactive monitoring and demonstrate high levels of patient engagement. Digital phenotyping, the measurement of individual technology usage, provides insight into individual behaviors associated with mental health. Objective Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Measures of mHealth use over time show that many users discontinue use within 3–6 months of initiation. 9–11 In fact, digital phenotyping studies have reported variable levels of engagement with mHealth which hampers the feasibility of phenotyping work 12 , 13 and may impair accuracy. 14 Prior work has identified correlates of mHealth use over time but findings are inconsistent between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of mHealth use over time show that many users discontinue use within 3–6 months of initiation. 9–11 In fact, digital phenotyping studies have reported variable levels of engagement with mHealth which hampers the feasibility of phenotyping work 12 , 13 and may impair accuracy. 14 Prior work has identified correlates of mHealth use over time but findings are inconsistent between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cogito Companion [56] Mental state prediction Sleep, mobility, and sociability Virtual Strength Within Me [57] Mental state prediction It does not infer information Ambient EuStress [58] Mental state prediction Mobility and sociability Positioning, inertial, virtual, and ambient Mood Triggers [59] Mental state classification Physical activity and mobility Positioning and inertial Data Collector [60]…”
Section: Positioning and Virtualmentioning
confidence: 99%
“…Many of these tools empower patients by enabling them to track their progress and become active participants in their healthcare journeys [27]. Moreover, many apps serve as useful methods for monitoring and facilitating early identification of risk and thus help mitigate negative psychiatric outcomes [28].…”
Section: Introductionmentioning
confidence: 99%